Business development for household scale liquid bath soap (Talenta Publisher, 2019)
Increasing the population automatically increases the demand for soap which encourages the development of soap production both by large, medium industries and home industries (IRT). The use of liquid bath soap shows an increasing trend but is not followed by an adequate production rate. This shows a huge market opportunity for the production and marketing of liquid bath soap. For this reason, community service is carried out to one of the household scale soap producers, which is one of the darma to the community. The soap production process by Mitra is still carried out manually using a paint bucket and a large wooden stirrer. This results in inefficient processes and low production rates. The packaging of soap products produced by Mitra is still very simple, using used aqua bottles so the selling price is also cheap. Unattractive packaging is feared to make products from Partners unable to compete in the market. In addition, Partners still do not have a Business Plan even though research activities in the field of product development are always carried out by Partners. This dedication activity offers a solution to overcome the above problems through technology transfer for the manufacture of liquid bath soap in the form of equipment procurement, liquid soap soap processing methods, product quality inspection in the laboratory, packaging procedures, and business management including in the case of making a business plan that can support financial independence. The soap quality test results show that the density and free alkali parameters have met the SNI. The level of respondents' preference for the product was also very positive. The product also does not provide an irritating effect for the user